IR reflectance characterization of glass-ceramic films obtained by high pressure impregnation of SnO2 nanopowders on float glass - Sequinel, T. [UNESP]; Cava, S.; Pimenta, J. O.; Pianaro, S. A.; Tebcherani, S. M.; Varela, José Arana [UNESP] (Elsevier B.V., 2011)
Glass-ceramic thin films of tin dioxide on float glass surfaces were obtained using a method based on high pressures and temperatures below the glass transition temperature. SnO2 thin films were confirmed using XRD, SEM and XRF techniques. These thin films were identified using IR reflectance due to a shift induced by Sn ion content of about similar to 100 cm(-1) in the main maximum peak position which is typical of stretching vibration intensities of a nu(Si-O-Si) bridging bonds, or a nu(Si-O-) nonbridging bonds. (C) 2011 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Nanostructures; Thin films; Glasses; Infrared spectroscopy